Adaptive Predictive Control of Dissolved Oxygen Concentration in a Dynamic Model of Whiteleg Shrimp Culture - Sacasqui, M (2017)
It introduces a dynamic model for dissolved oxygen content in an aquaculture system of whiteleg shrimp. Additionally, a non-linear controller has been designed for hourly control. This time frequency is necessary because of the time required to reach the predicted levels of oxygen. The dynamic model has incorporated a shrimp growth model calibrated with real data. The results show how the controller maintains the dissolved oxygen levels in the desired target, helping to improve production and minimize costs.